Menumbuhkan Perilaku dan Nilai Kewirausahaan Dalam Meningkatkan Kemandirian Bisnis di Kota Medan - Ahmad Rajin Siregar; Zuhrinal M. Nawawi (MES Bogor, 2023)
Perspectives and ways of behaving are the solidarity of an individual's personality which is framed by propensity ordinary. Pioneering conduct is impacted by inward and outer variables. These variables are possession freedoms (property right, PR), capacities/capabilities (skill/capacity,), and motivating forces while outside factors incorporate the climate in this way Attitudes and conduct can be changed without anyone else and/or there are natural tensions/impacts. there is an impact from inside themselves and from outside the climate to relate then develop indi mentalities and explicit ways of behaving. It is important to expect independent ventures' hardships by leading an exact concentrate on the enterprising soul, innovative qualities, and appraisal of pioneering conduct that might influence the acknowledgment of freedom endeavors. This study intends to investigate the impact of pioneering soul and enterprising qualities on innovative way of behaving to make business autonomy. The discoveries show that the pioneering soul impacts innovative way of behaving and positive roundabout impact on the business freedom. Keywords : Attitude, behaviour, entepreneurial spirit, to create business independence